ABNORMALITIES IN THE VERTEBRAL COLUMN OF INDIAN MACKEREL - Kulkarni, G M (Indian Journal of Fisheries, 2011)
Some abnormalities notiosd In the constituents of the vertebral columns of 9 specimens of mackerel are reported. These include ossified haemal braces farming plate-like structures, fused as well as closely apposed vertebrae, b’fid haemal spine, super-numerary neural and haemal arches and spines, absence of neural spine and fused proximal halves of neural spines which distally remain separate